Improved Math Learning Outcomes with Creative Problem Solving Model in Elementary School Students - Jusmawati, Jusmawati; Satriawati, Satriawati; R, Irman.; Rahman, Abdul; Arsyad, Nurdin (Budapest International Research and Critics University, 2021)
This research aims to improve the mathematical learning outcomes of elementary school students with a creative problem solving model. Methods used mix method approach with classroom action research. Classroom action research is deenisikan as a process of assessment of various learning activities carried out through four (4) stages which include: planning, implementation of actions, observation / collection of data, and reflection. Furthermore, these stages are arranged in a cycle of activities. The subject in this study was a student of class V Tunas Bangsa Kota Makassar which consisted of 30 students. The results showed that in cycle I the average score of student learning outcomes was 64.71 with a classical completion of 56.67% there was an increase in cycle II with the average score of student learning outcomes which was 87.75 with a classical completion of 93.33%. The results of learning cycle I to cycle II increased to achieve the classical completion indicator that is ≥ 80% of all students with KKM ≥ 70. This shows an increase in elementary school math learning outcomes with a creative problem solving model.